Historiografi Kajian Living Hadis di Indonesia - Ihsan, Muhammad Faqih; Ashshiddieqi, Muhammad Naufal (Journal of Hadith Studies, 2024)
The study of living hadith is a widely used approach to read hadith-based religious practices in society. However, in the last decade (2015–2023), findings show that research on living hadith tends to be stagnant because it focuses too much on the traditional aspects of practice, while the more complex aspects of transmission and transformation are still not paid attention. This shows that there are gaps and potential for further development in the study of living hadith, especially through a more diverse and in-depth approach. This research aims to map the trends, developments, and peculiarities of living hadith studies that have developed in Indonesia over the past ten years. Using the Systematic Literature Review (SLR) method, the author searched 21 academic literature with the keyword "living hadith" through a search engine for academic scientific works, such as; Google Scholar, Sinta, and Garuda which are then classified based on their themes and approaches. The results of this study show that the majority of living hadith studies in Indonesia during the period 2015–2023 still focus on practical and reception aspects, with descriptive methodological tendencies and minimal theoretical exploration. The aspect of transmission and transformation that is actually crucial in seeing the dynamics of the continuity of hadith in society has not been seriously touched. In addition, attention to the digital context as a new space for religious practice is also still very limited. Therefore, this study recommends the development of a living hadith study that is more reflective, interdisciplinary, and adaptive to social and technological changes.